Milk production and reproduction in cows with different proportions of Bos taurus x Bos indicus genes - Hernández, Arelis; Ponce de León, Raquel (Cuban Journal of Agricultural Science, 2016)
In order to evaluate genetic and environmental factors that influence on milk production and reproduction in cows with different proportions of Bos taurus x Bos indicus genes, an amount of 19,643 lactations of Mambí de Cuba (3/4 Holstein ¼ Zebu) cows and 15,925 lactations of Siboney de Cuba (5/8 Holstein 3/8 Zebu) cows were used, which belonged to three cattle farms, during the parturition years, from 1987 to 2012. The studied traits were accumulated milk production up to 305 d (L305), lactation duration (LD), milk production per day (MPD), period between parturition and gestation (PPG), period between parturitions (PP) and milk production per day during the period between parturitions (MPPP). A linear mix model was applied with the use of MIXED procedure of SAS. Fixed effects included genetic groups, herd, lactation number, year, parturition season, interactions of genetic group x lactation number, genetic group x parturition year and genetic group x parturition season. The cow nested in the herd and the error were considered as random effects. Mambí de Cuba and Siboney de Cuba cows showed similar reproductive performance and lactation duration. However, milk productions were superior in Mambí de Cuba cows in 84.43 kg, 0.29 kg/d and 0.69 kg/d, for L305, MPD and MPPP, respectively. It can be concluded that there was better milk performance in Mambí de Cuba and similar averages for reproductive periods and lactation duration. Key words: milk production, reproduction, genetic groups, environmental effects